Determinants of Rental Value for Residential Properties: A Land Owner’s Perspective for Boarding Homes - Wickramaarachchi, N.C. (Sri Lanka Institute of Architects, 2015)
Housing is the most representative land use in any urban area. At present renting of houses instead of buying is a significant phenomenon in the housing market. The ultimate goal of owning a rental property is to make profits with little additional effort. With the absence of a guideline, land owners arbitrary evaluate the property and charges unaffordable values. Since there is no alternative, depending on the need, tenant has to accept it. On the other hand, as each piece of property is unique, it is difficult to fix a rent. This becomes worse in boarding homes. With this background the focus of this paper is on developing an index as a guideline to determine the rental value in housing market. The case study specifies the renting based on higher education institute. Hence three types of renting units such as bed, room and annex selected. The data collection was completed through a structured questionnaire. The significant of each variable is evaluated through a multiple regression model. The findings categorized into levels on the basis of the coefficient values. The results indicate that distance to main junction is the most significant variable in the three types of properties.